(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The development of advanced materials for enhancing cement paste performance is crucial for improving construction efficiency and durability. This study investigates the use of thermo-responsive hydrogels, specifically poly (N-isopropylacrylamide) (PNIPAM) hydrogels, to address common issues in cement paste, namely workability and shrinkage. PNIPAM hydrogels exhibit unique temperature-sensitive properties, transitioning from hydrophilic to hydrophobic states around their lower critical solution temperature (LCST), which allows them to dynamically regulate moisture content. By incorporating PNIPAM hydrogels into cement paste, we aimed to enhance workability and reduce both plastic and hardened shrinkage. Experimental results reveal that the inclusion of PNIPAM hydrogels significantly improves the fluidity and ease of mixing of cement paste, while effectively mitigating shrinkage through their thermo-responsive behavior. The study demonstrates that PNIPAM hydrogels offer a versatile and effective solution for optimizing cement paste properties, providing substantial benefits in terms of improved handling and reduced cracking. These findings highlight the potential of thermo-responsive hydrogels to advance construction materials, contributing to more resilient and efficient concrete structures.